2019 Annual Report of the Kansas Poison Control Center at The University of Kansas Health System : 2019 KSPCC Report - Silver, Elizabeth; Oller, Lisa; White, Kathy; Coons, Doyle; Thornton, Stephen L (Kansas Journal of Medicine, 2021)
INTRODUCTION. This is the 2019 Annual Report of the Kansas Poison Control Center at The University of Kansas Health System (KSPCC). The KSPCC is one of 55 certified poison control centers in the United States and serves the state of Kansas 24-hours a day, 365 days a year with certified specialists in poison information and clinical and medical toxicologists. The KSPCC receives calls from the public, law enforcement, health care professionals, and public health agencies. All calls to the KSPCC are recorded electronically in the Toxicall® data management system and uploaded in near real-time to the National Poison Data System (NPDS) which is the data repository for all poison control centers in the United States. METHODS. All encounters reported to the KSPCC from 01/01/2019 through 12/31/2019 were analyzed. Data recorded for each exposure includes caller location, age, weight, gender, exposure substance, nature of exposure, route of exposure, interventions, medical outcome, disposition and location of care. Encounters were further classified as human exposure, animal exposure, confirmed non-exposure or information call (no exposure reported). RESULTS. The KSPCC logged 20,589 total encounters in 2019, including 19,406 human exposure cases. The KSPCC received calls from every county in Kansas. A slim majority of human exposure cases (50.5%, n=9,790) were female. Approximately 61% (n=11,876) of human exposures involved a child (defined as 19 years of age or less). Most encounters occurred at a residence (91.6%, n=17,780) and most cases (64.9%, n=12,599) originated from a residence. The majority of human exposures (85.5%, n=16,589) were acute cases (exposures occurring over 8 hours or less). Ingestion was the most common route of exposure documented (85.3%, n=16,548). The most common reported substance in pediatric (children ≤5) encounters was cosmetics/personal care products (n=959) followed closely by household cleaning product (n=943). For adult encounters, analgesics (n=1,296) and sedative/hypnotics/antipsychotics (n=1,084) were the most frequently involved substances. Unintentional exposures were the most common reason for exposures (75.4%, n=14,634). Most encounters (65.9%, n=12,780) were managed in a non-healthcare facility (i.e. a residence). Among human exposures, 14,591 involved exposures to pharmaceutical agents while 9,439 involved exposure to non-pharmaceuticals. Medical outcomes were 26.4% (n=5,116) no effect, 18.8% (n=3,652) minor effect, 9.3% (n=1,813) moderate effect, and 3.1% (n=603) major effects. There were 14 deaths in 2019 reported to the KSPCC. Cases from healthcare facilities, and cases with moderate or major medical outcomes and increased in 2019 compared to 2018. The number of deaths reported to the KSPCC increased in 2019 to 14 from 7 in 2018. CONCLUSIONS. The results of the 2019 Kansas Poison Control Center’s annual report demonstrate that cases are received from the entire state of Kansas totaling over 19,400 human exposures per year. While pediatric exposures remain the most common encounter, there continues an trend of increasing number of cases from healthcare facilities and for cases with serious outcomes. The experience of the KSPCC is comparable to national data. This report supports the continued value of the KSPCC to both public and acute health care in the state of Kansas.